Carrier frequency and incidence estimation of familial hemophagocytic lymphohistiocytosis in East Asian populations by genome aggregation database (gnomAD) based analysis - Park, Jong Eun; Lee, Taeheon; Ha, Kyeongsu; Cho, Eun Hye; Ki, Chang-Seok (Frontiers in Pediatrics, 2022)
Objectives: Hemophagocytic lymphohistiocytosis (HLH) is a clinical syndrome characterized by a life-threatening condition caused by severe hypercytokinemia. The hereditary forms of HLH, also called familial HLH (fHLH), have 4 different genes (PRF1, UNC13D, STX11, and STXBP2) and have been identified as being causative for fHLH. This study aimed to analyze the carrier frequency and expected incidence of fHLH in East Asians and Koreans using exome data from the Genome Aggregation Database (gnomAD). Methods: We analyzed 9,197 exomes for East Asian populations from gnomAD with 1,909 Korean for four fHLH genes. All identified variants were classified according to 2015 American College of Medical Genetics and Genomics and the Association for Molecular Pathology guideline. Results: 19 pathogenic variant/likely pathogenic variants (PV/LPVs) were identified in 30 East Asian individuals (0.33%). Among them, 7 PV/LPVs were identified in 17 Korean individuals (0.63%). The estimated incidence of fHLH was 1 in 1,105,652 for East Asians and l in 235,128 for Koreans. Conclusions: This study is the first to identify carrier frequencies in East Asian and Korean populations for fHLH using gnomAD. It was confirmed that the carrier frequency of fHLH patients was high in Koreans among East Asians and the incidence was also predicted to be higher than that of other East Asians. The variant spectrum of fHLH genes in East Asian and Korean populations differed greatly from those of other ethnic groups.